The Perception of Fisherman in The Burau Pantai, District of Burau, East Luwu Regency for The Importance of Formal Education - Mudiyana, Kadek; Wahid, Abdul; Cangara, Arie Syahruni (PONGGAWA : Journal of Fisheries Socio-Economic, 2024)
This research aims to determine the characteristics of the education level of fishermen in Burau Pantai Village, Burau District, East Luwu Regency and to find out fishermen's perceptions of formal education and to find out what fishermen do in continuing their children's formal education. This research was carried out in November 2020 - December 2020 in Burau Pantai Village, Burau District, East Luwu Regency, South Sulawesi. The sampling method used was Non Probability sampling. The data sources used were primary data and secondary data. The data analysis used percentage analysis. Education, Likersts scale and qualitative data analysis. Educational characteristics of fishermen in Burau Pantai Village as many as 87 people did not take formal education This is influenced by many factors, especially fishermen's socio-economic factors. Public perception of children's formal education where fishermen choose that education will determine profession and work In the future, fishermen choose that education will make someone knowledgeable, fishermen's assumptions about the cost of education can be cultivated, there are no fishermen who say that education is cheap, fishermen say that education can change the status and position of fishermen social. Various efforts have been made by fishermen in meeting the educational needs of their children, namely the double income pattern.